2008
DOI: 10.1007/s10157-007-0017-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen treatment augments the efficacy of cilazapril and simvastatin regimens in an experimental nephrotic syndrome model

Abstract: Both cilazapril and simvastatin regimens improve oxidative stress and proteinuria, while the effects significantly increase with the combination of HBO treatment. HBO seems to be a candidate antioxidant strategy in glomerular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…GPX may play an important role in the protection of extracellular fluid component and cell surface against peroxide mediated damage; in this sense, any reduction in its activity will therefore result in increased lipid peroxidation. Studies with humans (Ceballos-Picot et al, 1996;Zachara et al, 2004Zachara et al, , 2006 and animals (Sonmez et al, 2008) indicate a gradual decrease in GPX activity with progression of the renal disease possibly due to the fact that this enzyme is synthesized predominantly in the kidney. Our results showed no significant change in GPX activity after renal injury, but a significant increase in activity was observed in animals with CKD exposed to exercise (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…GPX may play an important role in the protection of extracellular fluid component and cell surface against peroxide mediated damage; in this sense, any reduction in its activity will therefore result in increased lipid peroxidation. Studies with humans (Ceballos-Picot et al, 1996;Zachara et al, 2004Zachara et al, , 2006 and animals (Sonmez et al, 2008) indicate a gradual decrease in GPX activity with progression of the renal disease possibly due to the fact that this enzyme is synthesized predominantly in the kidney. Our results showed no significant change in GPX activity after renal injury, but a significant increase in activity was observed in animals with CKD exposed to exercise (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In experimental nephrology (rats), HBOT has been used in acute kidney injury and ischemia/reperfusion models, cisplatin-and cyclosporine-related nephrotoxicity, and nephrotic syndrome [32][33][34][35]. In clinical nephrology, HBOT was used in cutaneous ulcers due to calciphylaxis, chronic osteomyelitis, hemorrhagic cystitis, and renal zygomycosis [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Yilmaz et al found that HBOT has a synergistic effect with an angiotensin receptor blocker to reduce proteinuria in the adriamycin rodent model of focal segmental glomerulosclerosis (FSGS) [5]. Sonmez et al found the same with an angiotensin-converting enzyme inhibitor [6]. Several studies in rat models of ischemia perfusion injury found beneficial effects of HBOT on histological and biochemical markers of injury.…”
Section: Discussionmentioning
confidence: 99%
“…ese same factors are implicated in the pathogenesis of microvascular complications of diabetes in the eye and in the kidney [3]. is suggests HBOT might be potentially harmful for patients with diabetes; however, animal studies show reduced proteinuria with HBOT treatments [4][5][6]. Virtually, no clinical data exist on the effect of HBOT on proteinuria and renal function in patients with diabetes mellitus, despite its widespread use in these patients.…”
Section: Introductionmentioning
confidence: 99%